A semiphysiological pharmacokinetic model for artemisinin in healthy subjects incorporating autoinduction of metabolism and saturable first‐pass hepatic extraction - Gordi, Toufigh; Xie, Rujia; Huong, Nguyen V.; Huong, Dinh X.; Karlsson, Mats O.; Ashton, Michael (British journal of clinical pharmacology, 2005)
Aims Previous studies have shown that the antimalarial drug artemisinin is a potent inducer of its own metabolism in both patients and healthy subjects. The aim of this study was to characterize the time‐dependent pharmacokinetics of artemisinin in healthy subjects. Methods Twenty‐four healthy males were randomized to receive either a daily single dose of 500 mg oral artemisinin for 5 days, or single oral doses of 100/100/250/250/500 mg on each of the first 5 days. Two subjects from each group were administered a new dose of 500 mg on one of the following days after the beginning of the study: 7, 10, 13, 16, 20, or 24. Artemisinin concentrations in saliva samples collected on days 1, 3, 5, and on the final day were determined by HPLC. Data were analysed using a semiphysiological model incorporating (a) autoinduction of a precursor to the metabolizing enzymes, and (b) a two‐compartment pharmacokinetic model with a separate hepatic compartment to mimic the processes of autoinduction and high hepatic extraction. Results Artemisinin was found to induce its own metabolism with a mean induction time of 1.9 h, whereas the enzyme elimination half‐life was estimated to 37.9 h. The hepatic extraction ratio of artemisinin was estimated to be 0.93, increasing to about 0.99 after autoinduction of metabolism. The model indicated that autoinduction mainly affected bioavailability, but not systemic clearance. Non‐linear increases in AUC with dose were explained by saturable hepatic elimination affecting the first‐pass extraction. Conclusion Artemisinin produces a rapid onset of enzyme induction, resulting in a decrease in its own bioavailability over time. The proposed model successfully described the time‐course of the onset and normalization of the autoinduction of metabolism in healthy subjects receiving two different dosage regimens of the compound.